Germinação e morfoanatomia do desenvolvimento pós-seminal de espécies de Vellozia Vand. de campos rupestres brasileiros - Silva, Shelka Alcântara da (2013)
Velloziaceae is a relatively small family from Pandanales, including approximately 250 species that are very common in the brazilians campos rupestres . The Velloziaceae have a high degree of endemism, and some species are threatened with extinction. Several species of Velloziaceae have potential ornamental use, both for plant architecture as the foliage, or due to the beauty of their flowers. However, few studies investigate the germinative behavior and the post-seminal development of these species. In order to contribute with the knowledge of the germination and post-seminal development of Velloziaceae were analyzed seeds of twelve species of Vellozia Vand. from Minas Gerais and Goiás campos rupestres . The seeds were sown in Emanueli chambers and the experiments were installed in germination chamber under controlled light and temperature. The data about germinative behavior and post-seminal development morphology and anatomy were obtained using the usual techniques for each case. The seeds of the studied species are small, preferentially photoblastic and most of them exhibit high germinability (G ≥ 60%) and high values of mean germination rates (0,06 ≤ v ≤ 0,21 day-1). The coefficient of variation of the germination time and the measurements of uncertainty and synchrony revealed that the species can be separated in two groups: in the first group are the species exhibiting heterogeneous and spread germination through the time and in the second group were coupled the species exhibiting homogenous germination more concentrated over time. The photoblastism and fast germination, yet spread in time, suggest relative dormancy, which is common in seeds from species adapted to adverse environmental conditions and indicate that the seeds of these species can form seed banks. The seeds are small and bitegumented. The embryo is small and exhibits a single vascular bundle in the cotyledon. Germination begins with the protrusion of the cotyledon s base and radicle and the seedling is criptocotylar. The primary root is persistent and forms lateral roots. Eophyll and methaphyll are similar. Seedling vascularization is reduced. The Vellozia exhibited similar morphological and anatomical characters during the post-seminal development, which reinforces the genera identity.